SCIENTIFIC AND ORGANIZATIONAL ASPECTS OF FORMATION EXPENSES FOR STATE VARIETY TESTING VARIETIES WINTER WHEAT - Плаксієнко, В. Я.; Гладіліна, Т. В. (Scientific Progress & Innovations, 2014)
The paper is to form the pattern of expenditure for state variety trials in winter wheat breeding and research institutions (based on the selection center PGAA) and considered legal security of the State variety testing of plant varieties in Ukraine to diagnose and improve the ways of forming the costs of creating varieties with using innovative methods of breeding wheat affecting the discharge of the selection process in space and time, to reduce the costs of the selection process, the effective use of high-quality plant resources, breeding institutions and enhance scientific and technological level of grain production.